[PP.09.21] PULSE WAVE VELOCITY WITHOUT PREVIOUS CARDIOVASCULAR EVENTS. (September 2017) - Pinto, S.; Pires, J.; Ferreira, F.; Teixeira, M.; Ribau, V.; Neves, C.; Bastos, J. Mesquita
Abstract : Objective: Pulse wave velocity (PWV) is considered a marker of cardiovascular (CV) risk prognosis. The authors aimed to evaluate an hypertensive group of hypertensive patients who was submitted to PWV and to study association between this indicator and other features. Design and method: Retrospective study of all hypertensive patients evaluated by PWV in a Portuguese average-size hospital Arterial Hypertension Consultation (n = 373). Continuous variables are expressed as mean and were compared using the unpaired Student's t-test. Categorical variables are expressed as frequencies and percentages and were compared using the chi-squared test. Results: Considering the 373 patients (188 men, 52.8%), the means of age (55.06 years ± 15.21), systolic blood pressure (BP) (144.20 mmHg ± 19.63), systolic BP24 hours (125.96 mmHg ± 11.54), diastolic BP24 hours (75.65 mmHg ± 8.33) and body mass index (28.38 Kg/m 2  ± 4, 67) were calculated. Comparing the group of patients with PWV>10 m/s with the patients with lower PWV, the first had higher age (65.08 ± 10.56 versus 50.59 ± 14.78 years), higher prevalence of male (64.00% versus 47.8%, p = 0.00), higher prevalence of previous event (18.0% versus 9%, p = 0.014), diabetes (49.5% versus 17.6%, p = 0.00) and dyslipidemia (79.3% versus 57.1%, p = 0.000). It also had higher prevalence of diastolic dysfunction (61.2% versus 25.2%, p = 0.00) and fall of nocturnal blood pressure (43.3% versus 64.3%, p = 0.041). Considering the refractory blood pressure patients, in the group with higher PWV, there was a prevalence of 31.5% versus16.3% in the lower PWV group (p = 0.001) Conclusions: PWV may enable better recognition of high-risk populations that might benefit from more aggressive CV disease risk factor management.